Development of the sources of mathematics online learning self-efficacy scale (SMOLSES) for SDGs quality education - Nurhayati, Suci; Kandaga, Thesa; Gusti, Valeria Yekti Kwasaning; Mohamad, Liana (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Background: The expansion of online learning in open and distance education poses new challenges in understanding students’ self-efficacy, particularly in mathematics, a subject that demands both cognitive engagement and emotional resilience. Existing instruments have not adequately captured the distinct sources of self-efficacy relevant to this setting, necessitating the development of a context-specific measurement scale Aim: This study aims to develop and validate the SMOLSES, an instrument designed to assess the sources of self-efficacy, mastery experience, vicarious experience, social persuasion, and physiological state in the context of online mathematics learning for distance education students. Method: The scale was developed using a questionnaire administered to 105 Mathematics Education students at Universitas Terbuka. Partial Least Squares analysis was used to evaluate the measurement and structural models. The results supported the reliability and validity of the scale, confirming 28 valid items across five constructs. Structural model analysis revealed that physiological state and social persuasion significantly predicted students' belief in their self-efficacy, while vicarious experience showed the strongest correlation with academic performance. Result: SMOLSES provides a reliable tool for diagnosing students’ readiness and guiding instructional design in online mathematics learning. The findings emphasize the importance of social and emotional factors in shaping self-efficacy and learning engagement, particularly in asynchronous environments where peer modeling and support mechanisms are critical. Conclusion: By addressing a critical measurement gap, this study contributes to advancing quality and inclusive education (SDG 4). SMOLSES can inform data driven interventions that enhance student engagement and achievement in open and distance learning settings.